IMPLEMENTASI METODE BOOTSTRAP DALAM INFERENSI TITIK-TITIK BIPLOT AMMI MODEL AMMI CAMPURAN (MIXED AMMI) (Studi Kasus: Menduga Stabilitas Genotipe Padi) - TRISNAYANTI, NI PUTU AYU DINITA; SUKARSA, I KOMANG GDE; SUCIPTAWATI, NI LUH PUTU (E-Jurnal Matematika; Vol 4 No 3 (2015)DO - 10.24843/MTK.2015.v04.i03.p098, 2015)
In this research bootstrap methods are used to determine the points inference of biplot figures on the analysis of AMMI. If the environmental factors are assumed to be random factors, then Mixed AMMI is used as a model of analysis.  In the analysis of the stabilit, the main components score interaction used are KUI 1 and KUI 2 . The purpose of this study is to determine the Biplot figures based on two scores these are KUI with the greatest diversity of Mixed AMMI models and the points inference by using the bootstrap method. The stable genotypes obtained from biplot AMMI 2 are G 1 , G 5 , and G 6 . Based on points inference of each genotype, G 1 and G 5 can be regarded as the most stable genotype. This is because the distribution of G 1 and G 5 are the closest to the center point (0,0) and both of them have  a small radius.
Keywords: Bootstrap, AMMI, Mixed AMMI, biplot